Desenvolvimento de leite fermentado caprino com potencial probiótico adicionado de farinha de xique-xique (Pilosocereus gounellei): propriedades tecnológicas, nutricionais, sensoriais e funcionais - Dantas, Dalyane Laís da Silva (2021)
This study evaluated the impact of adding different concentrations (1.0 and 2.0%) of xique xique flour on the technological, nutritional and bioactive properties, the protective effect on the survival of the autochthonous strain Limosilactobacillus mucosae CNPC007 during simulated gastrointestinal digestion in goat fermented milks, as well as the acceptance and sensory characteristics (Just about Right) of the products during the refrigerated storage (4 ± 1 ºC). It was observed that the treatments LFX1% and LFX2% showed greater intensity in terms of yellow coloration and increased brightness throughout storage when compared to LFC. There was an increase in the percentage of viscosity for the LFX1% and LFX2% treatments compared to conventional yogurt until the 14th day of refrigerated storage. A reduction in total sugar content and an increase in protein content were observed throughout the refrigerated storage for most of the formulations, with higher production of lactic malic and propionic acid for the yogurts added from the xique-xique flour. After 28 days of storage, LFX2% showed higher counts of L. mucosae CNPC007, mineral contents, total phenolic compounds, flavonoids and antioxidant activity. After simulated digestion, L. mucosae CNPC007 showed higher numbers of viable cells for LFX1% and LFX2% formulations when compared to LFC, indicating the possible protective effect of the xique-xique flour during the digestion steps, with counts >7 log CFU/g. According to the sensory analysis with the JAR scale, the samples with added xique-xique flour obtained better results (p < 0.05) for the goat aroma parameter (LFX1%, 3.29 ± 0.83 and LFX2%, 3.48 ± 1.07). In addition, the tasters were indifferent to the herbaceous aroma and flavor characteristics. The xique-xique flour can be used for the production of a new goat fermented milk added of autochthonous probiotic strain L. mucosae CNPC007 without negatively affecting the technological, sensory characteristics, exerting a protective effect on the added probiotic, adding nutritional and functional value to the product, making it an option for the functional dairy products industry.